Human immunodeficiency virus type 1 Vpu protein induces degradation of CD4 in vitro: the cytoplasmic domain of CD4 contributes to Vpu sensitivity. - Chen, M Y (1993)
CD4 is an integral membrane glycoprotein which functions as the human immunodeficiency virus (HIV) receptor for infection of human host cells. We have recently demonstrated that Vpu, an HIV type 1 (HIV-1) encoded integral membrane phosphoprotein, induces rapid degradation of CD4 in the endoplasmic reticulum. In this report, we describe an in vitro model system that allowed us to define important parameters for Vpu-dependent CD4 degradation. The rate of CD4 decay in rabbit reticulocyte lysate was approximately one-third of that observed previously in tissue culture experiments in the presence of Vpu (40 versus 12 min) and required no other HIV-1 encoded proteins. Degradation was contingent on the presence of microsomal membranes in the assay and the coexpression of Vpu and CD4 in the same membrane compartment. By using the in vitro degradation assay, the effects of specific mutations in CD4, including C-terminal truncations and glycosylation mutants, were analyzed. The results of these experiments indicate that Vpu has the capacity to induce degradation of glycosylated as well as nonglycosylated membrane-associated CD4. Truncation of 13 C-terminal amino acids of CD4 did not affect the ability of Vpu to induce its degradation. However, the removal of 32 amino acids from the C-terminus of CD4 completely abolished sensitivity to Vpu. This suggests that Vpu targets specific sequences in the cytoplasmic domain of CD4 to induce its degradation. We also analyzed the effects of mutations in Vpu on its biological activity in the in vitro CD4 degradation assay. The results of these experiments suggest that sequences critical for this function of Vpu are located in its hydrophilic C-terminal domain.